Formulation of Lotion Preparation From Basil Leaf Extract (Ocimum Basilicum) as an Anti Mosquito Repellent - Zalianti, Vena; Muhammad Tasjiddin Teheni; Yayuk Sri Rahayu (International Journal of Multidisciplinary Learners, 2025)
Basil plant ( Ocimum basilicum ) is one of the traditional medicinal plants known to have various properties. Basil leaves ( Ocimum basilicum ) contain compounds such as saponins, flavonoids, tannins and essential oils, where flavonoids have toxic properties through their sharp aroma. The purpose of this study was to determine the formulation of making basil leaf extract lotion ( Ocimum basilicum ) as a mosquito repellent, using the maceration method. The results of the study showed that formula 1 preparation did not have basil leaf extract ( Ocimum basilicum ) so that in this preparation the skin was often infested by mosquitoes, formula 2, namely the preparation that had basil leaf extract ( Ocimum basilicum ) 1% in this preparation mosquitoes still landed on the skin, formula 3, namely the preparation that had basil leaf extract ( Ocimum basilicum ) 3% in this preparation mosquitoes were rarely or few landed on the skin and formula 4 with basil leaf extract ( Ocimum basilicum ) 5% in this preparation mosquitoes did not land on the skin. In this study basil leaf extract ( Ocimum basilicum ) can be an anti-mosquito lotion formula. A good and effective lotion as an anti-mosquito is found in formula 4 with basil leaf extract ( Ocimum basilicum ) 5%. The test results met the physical stability test requirements, but not for the spreadability test, with formula 4 as the most effective with 5% active substance.